Comparison of the Different Definition Criteria for the Diagnosis of Amniotic Fluid Embolism - Hiroshi Kobayashi (Journal of Clinical and Diagnostic Research, 2017)
Introduction: There are several sets of criteria for the diagnosis of Amniotic Fluid Embolism (AFE), but little is known about their degree of agreement. Aim: To evaluate the concordance of the Japan criteria for AFE in comparison with two definitions: the US AFE registration entry criteria (the US criteria) and UK Obstetric Surveillance System criteria for defining cases of amniotic fluid embolism (the UK criteria). Materials and Methods: A retrospective observational study was conducted in which the AFE cases registered in the Obstetrical Gynaecological Society of Kinki District in Japan for the period of April 2005 to December 2012 have been analysed by the expert steering obstetric committee, organized by the members of the Obstetric Research group. Cohen's kappa coefficient was used to calculate the agreement among three clinical diagnoses. For inter-group comparison, the Pearson Chi-square test was used (for categorical) and Mann-Whitney test was used (for continuous variables). Results: Among the 26 cases registered for this period, a total of 18 women were selected as having AFE according to the Japan criteria. Five women died (case fatality rate 27.8%). Agreement between the Japan criteria and the US and UK criteria was k = 0.453 and k = 0.538, respectively, reflecting moderate agreement. However, only 38.9% were given a diagnosis of AFE according to all three criteria. The factor that most often caused disagreement in diagnosis between the Japan criteria and the US criteria was “onset within 30 minutes postpartum”. The UK criteria excluded “women with postpartum haemorrhage as the first presenting feature in whom there was no evidence of cardiorespiratory compromise”. The case fatality rates in US and UK are higher than in Japan (50.0% and 38.5% vs 27.8%), but this did not result in a significant difference (p=0.497). Conclusion: The groups of subjects identified as having AFE by the Japan criteria had a medium agreement with the US (k=0.453) or UK criteria (k=0.538). These three definition criteria identified different subgroups of patients. Such disagreement has serious implications for research and treatment.